Asbestos exposure and malignant mesothelioma of the tunica vaginalis testis: a systematic review and the experience of the Apulia (southern Italy) mesothelioma register - Luigi Vimercati; Domenica Cavone; Maria Celeste Delfino; Luigi De Maria; Antonio Caputi; Giovanni Maria Ferri; Gabriella Serio (Environmental Health, 2019)
Abstract Background Malignant mesothelioma of the tunica vaginalis testis (MMTVT) is a rare disease with a poor prognosis. The diagnosis and management of these lesions are often difficult for pathologists, surgeons, oncologists and occupational physicians. A preoperative diagnosis of malignancy is rarely made, and there is no established effective therapy except orchidectomy. Methods A systematic literature review was conducted among the articles published in the English literature on primary MMTVT. Moreover four cases from the Apulia mesothelioma register are reported here. Results Two hundred eighty-nine cases of MMTVT have been reported from 1943 to 2018. Overall asbestos exposure has been investigated only for 58% of all cases reported in this review, while in 41.8% this data are not available. Noteworthy is the fact that in many reports there is not an anamnestic reconstruction of any asbestos exposure. A history of direct occupational, environmental or familial asbestos exposure is found in 27.6% of the cases. The four cases from the Apulia mesothelioma register are all with ascertained occupational exposure to asbestos. Conclusions The true incidence of asbestos exposure in MMTVT is underestimated because of insufficient information reported in older literature. To establish a broad consensus on the causal relationship between asbestos and MMTVT in the scientific community its necessary to analyze the same variables in the epidemiological studies. In general it should be recommended that a positive history of exposure to asbestos or to asbestos–containing materials are at risk for the development of a MMTVT and should be monitored.